Investigating Social Stigma of Children with Intellectual Disabilities - Ketrin; Hana Ainiyah; Hani Khairunnisa; Mochamad Ramadhan Gunawan; Amanda Aulia; Citra Ashri Maulidina; Mohammad Arif Taboer (International Disability Innovation Journal, 2025)
Social stigma towards children with intellectual disabilities is a complex issue that impacts the psychological, social, and educational aspects of children and their families. Society often labels them negatively, excludes them, and judges them as incapable of developing, due to a lack of understanding and awareness of these children’s potential. This literature review aims to systematically examine how social stigma is formed, its impact on children and families, and strategic efforts to reduce it. This study employs a systematic literature review method, drawing on ten scientific articles published between 2020 and 2025, sourced from national and international databases. The analysis was conducted descriptively to identify patterns, forms of stigma, and relevant intervention strategies. The results show that social stigma against children with intellectual disabilities remains strong, both in schools, the general community, and the workplace. The impacts include low self-confidence, social isolation, limited access to education and public services, and emotional pressure on parents. However, there are also positive efforts such as inclusive school programs, social communities, and initiatives by the government and social institutions that are beginning to build public awareness.